University Instructors' Perceptions of Higher Education: Psychosemantic Approach - Sorokova M.G. (Психолого-педагогические исследования)
The digitalization processes in higher education are a stable global trend. Digital competencies are very relevant for specialists in all subject areas; this is a demand of the modern digital economy and labor market. The digitalization of education is a complex multidimensional process that is estimated differently by university instructors. The purpose of the empirical study: to reveal the peculiarities of the ideas about higher education of university instructors who do not use and do use e-learning courses in their professional activities. The research is a pilot study, the findings are preliminary and will be tested on larger samples. Group semantic spaces for both categories of respondents were constructed by the method of semantic differential using factor analysis. (1) In both categories, there is a factor that reflects the most attractive qualities of higher education, but the set of these qualities is different. Both categories of respondents are characterized by a factor reflecting the problems and shortcomings of higher education, but they put different meanings into it. (2) For instructors who do not use e-courses, most socially accessible and technically equipped approaches, such as distance learning, e-courses, massive open online courses, are subjectively unattractive. Blended learning is more in line with their ideas about quality of higher education, but the most subjectively attractive are the project method and traditional face-to-face learning. (3) Instructors using e-courses are characterized by the recognition of the problematic nature of distance learning, e-courses, massive open online courses, but at the same time of their social accessibility, combined with convenience for instructor and subjective attractiveness. Blended learning is less problematic, socially inaccessible, but subjectively also very attractive. The project method is a promising approach that has few drawbacks, but is also socially inaccessible and less convenient for the instructor. (4) For instructors who do not use e-courses, traditional face-to-face education is the least technically equipped, having problems and shortcomings, but subjectively very attractive. For instructors using e-courses, this approach, on the contrary, has few problems, is convenient for the instructors and is socially accessible, but subjectively it does not arouse interest and does not correspond to their ideas about the quality of higher education.